Beneficial Effect of Bariatric Surgery on Abnormal MMP-9 and AMPK Activities: Potential Markers of Obesity-Related CV Risk - García-Prieto, Concha F.; Gil-Ortega, Marta; Vega-Martín, Elena; Ramiro-Cortijo, David; Martín-Ramos, Miriam; Bordiú, Elena; Sanchez-Pernaute, Andrés; Torres, Antonio; Aránguez, I.; Fernández-Alfonso, María; Rubio, Miguel A.; Somoza, Beatriz (Frontiers in Physiology, 2019)
Bariatric surgery (BS) results in sustained weight loss and may reverse inflammation, metabolic alterations, extracellular matrix remodeling and arterial stiffness. We hypothesized that increased stiffening in omental arteries from obese patients might be associated with an increase in MMP activity and a decrease in p-AMPK, together with systemic oxidative stress and inflammation. Moreover, BS could contribute to reversing these alterations. This study was conducted with 38 patients of Caucasian origin: 31 adult patients with morbid obesity (9 men and 22 women; mean age 46 years and BMI = 42.7 ± 1.0 kg/m2) and 7 non-obese subjects (7 women; mean age 45 years and BMI = 22.7 ± 0.6 kg/m2). Seventeen obese patients were studied before and 12 months after BS. The stiffness index β, an index of intrinsic arterial stiffness, was determined in omental arteries and was significantly higher in obese patients. Levels of phosphorylated AMPK (p-AMPKThr-172) and SIRT-1 were sig¬nificantly lower in peripheral blood mononuclear cells (PBMCs) from obese patients than those from non-obese patients (p<0.05) and were normalized after BS. Total and active MMP-9 activities, LDH, protein carbonyls and uric acid were higher in obese patients and reduced by BS. Moreover, there was a correlation between plasmatic LDH levels and the stiffness index . BS has a beneficial effect on abnormal MMP-9, LDH and AMPK activities that might be associated with the development of arterial stiffness in obese patients. Since these parameters are easily measured in blood samples, they could constitute potential biomarkers of cardiovascular risk in morbid obesity.